MANAJEMEN KINERJA APARATUR DESA DALAM MEWUJUDKAN PEMBANGUNAN DI DESA TAENG KECAMATAN PALLANGGA KABUPATEN GOWA (Jurnal Washiyah: Jurnal Kajian Dakwah dah Komunikasi, 2020)
The results showed that the performance management of village apparatus in realizing development in Taeng village Pallangga subdistrict Gowa regency, namely; 1) In carrying out an activity including, planning and supervision that has been applied by the village apparatus so that in carrying out the activities will be easy. Supervising and input are also carried out by the village government of the village apparatus in improv services to the community. While the development in Taeng village Pallangga district Gowa regency can be said to be successful. The construction of the paving block, plate duikers, construction of posyandu, and construction of family toilets greatly helped the community. Then the village of Taeng by holding training and recruitment aimed at developing community creativity.